Popular Music as an Interpretive Device for Creating Meaningful Visitor Experience in Music Museums - Wiens, Kathleen (Ethnologies, 2015)
This article looks at modes of visitor engagement in a music museum setting. As curator for a gallery and collection of European music, I am tasked with representing musical cultures in Europe according to geo-political entity, community group, and genre. I present a case study in which popular music served to connect visitors with display content by instigating interest and creating a sense of personal context for the visitor. By presenting visitors with audio-visual content that was meaningful to them I was able to increase visit length to specific displays. In these cases, I used popular music as a didactic tool to guide visitors towards critical understandings of culture. It allowed me to simply and effectively represent nuances of musical behaviour and concepts of locality, innovation, and fluidity. Findings of the project stimulated thoughts and questions regarding the purposes and methods of representation within musical instruments museum display spaces.